Isolated Attosecond Pulse Generation in a 800 nm Laser Field by Adding a Terahertz (THz) Pulse (Journal of Atomic and Molecular Sciences, 2016)
We theoretically study the high-order harmonic and the isolated attosecondpulse generation in the near-infrared (IR) (3-fs, 800 nm) laser pulse by adding a terahertz(THz) controlling field with proper phases. It is found that the high-order harmonicspectrum in the IR pulse by adding a terahertz field is broader and smootherthan that in the single IR pulse. The underlying physical mechanism is illustrated bymeans of the time-frequency analysis and the three-step model. We calculate the ionizationrate by ADK model to further demonstrate the process of high-order harmonicgeneration. By superposing a proper range of harmonic spectrum, an isolated attosecondpulse with the duration of 71 as is obtained.